2022
DOI: 10.1007/s11250-022-03410-5
|View full text |Cite
|
Sign up to set email alerts
|

Devising a selection strategy for the Jamunapari goat for improving lactation performance

Abstract: This study aims to evaluate the genetic potential of the Jamunapari goat and formulate a new selection strategy for improving the lactation traits. The data set included 4049 phenotypic records for lifetime milk yield at 90 days (MY90) and 140 days (MY140), total milk yield (TMY), and lactation length (LL) obtained from the progeny of 83 sires and 1643 dams between 1990 and 2019. Animal model employing average information restricted maximum likelihood (AIREML) was used to estimate genetic parameters for milk y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…These maternal heritability estimates were influenced by a large negative estimate of covariance between additive genetic and maternal effects. Similar findings regarding the significance of the maternal component have been reported in previous studies, such as in the estimation of total lactation yield in Jamunapari goats (Rout et al, 2017) and lactation length (Dige et al, 2022).…”
Section: Estimates Of (Co)variance Components For First Parity Produc...supporting
confidence: 90%
See 4 more Smart Citations
“…These maternal heritability estimates were influenced by a large negative estimate of covariance between additive genetic and maternal effects. Similar findings regarding the significance of the maternal component have been reported in previous studies, such as in the estimation of total lactation yield in Jamunapari goats (Rout et al, 2017) and lactation length (Dige et al, 2022).…”
Section: Estimates Of (Co)variance Components For First Parity Produc...supporting
confidence: 90%
“…Higher heritability estimates as compared to the present study for lactation traits have been reported across several breeds ranging from 0.22 to 0.30 (Boichard et al, 1989;Dige et al, 2022;Rout et al, 2017;Singh et al, 2021;Valencia et al, 2006). These findings underscore the variability in heritability estimates for these traits, which can be influenced by factors such as breed, selection pressure and the genetic makeup of the studied populations.…”
Section: Estimates Of (Co)variance Components For First Parity Produc...supporting
confidence: 53%
See 3 more Smart Citations